Peripherally inserted central catheters versus non-tunnelled ultrasound-guided central venous catheters in newborns: a retrospective observational study - Prem Chandra; Mohammad A A Bayoumi; Roland van Rens; Deena Shaltout; Ashraf Gad; Einas E Elmalik; Samer Hammoudeh (BMJ Open, 2022)
Objectives We aimed to compare the success rates and other catheter-related parameters between peripherally inserted central catheters (PICCs) and non-tunnelled ultrasound-guided central venous catheters (USG-CVCs) including femoral, jugular, brachiocephalic and subclavian lines.Design This was a retrospective observational study.Setting The study was performed in a level III neonatal intensive care unit (NICU) in Qatar, as a single-site study.Participants This study included 1333 neonates who required CVC insertion in the NICU from January 2016 to December 2018. Of those, we had 1264 PICCs and 69 non-tunnelled USG-CVCs.Outcome measures The success rate and other catheter-related complications in the two groups.Results The overall success rate was 88.4% in the USG-CVCs (61/69) compared with 90% in the PICCs (1137/1264) group (p=0.68). However, the first prick success rate was 69.4% in USG-CVCs (43/69) compared with 63.6% in the PICCs (796/1264) group. Leaking and central line-associated blood stream infection (CLABSI) were significantly higher in the USG-CVC group compared with the PICC group (leaking 16.4% vs 2.3%, p=0.0001) (CLABSI 8.2% vs 3.1%, p=0.03). CLABSI rates in the PICC group were 1.75 per 1000 catheter days in 2016 and 3.3 in 2017 compared with 6.91 in 2016 (p=0.0001) and 14.32 in 2017 (p=0.0001) for the USG-CVCs. USG-CVCs had to be removed due to catheter-related complications in 52.5% of the cases compared with 29.9% in PICCs, p=0.001. In 2018, we did not have any non-tunnelled USG-CVCs insertions in our NICU.Conclusions The overall complication rate, CLABSI and leaking are significantly higher in non-tunnelled USG-CVCs compared with the PICCs. However, randomised controlled trials with larger sample sizes are desired. Proper central venous device selection and timing, early PICC insertion and early removal approach, dedicated vascular access team development, proper central venous line maintenance, central line simulation workshops and US-guided insertions are crucial elements for patient safety in NICU.